Penyuluhan Etika Batuk Yang Benar Sebagai Upaya Pencegahan Penyakit TB Paru Di SDN 03 Kamcar - Nasution, Dina Rahmi Solihad; Lubis, Yuni Aflah; Liana; Nina Nazlina; Dalimunthe, Maharani; Nasution, Izmi Fadhilah (Universitas Aufa Royhan Di Kota Padangsidipuan, 2024)
Nowadays,Tuberculosis is still a global health problem, especially in developing countries including Indonesia. Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis which attacks the lungs. Although it is contagious, TB disease can be prevented by giving an explanation to the patient to cover the mouth with a handkerchief if coughing and not to spit or discharge phlegm in any place and provide a place to spit that is given recommended materials. The purpose of this community service activity is to provide education to Elementary School pupils and increase knowledge about good and correct cough etiquette as an effort to prevent pulmonary TB disease. The implementation method was carried out by giving lectures and brochure and banner media, the participant of this community service is the students of Elementary School Kamcar 03 Padangsidimpuan. The result of this activity is classified by the level of knowledge of elementary school students about the correct cough ethics. Before being given counseling, participant who classified as lack of those knowledge are 12 participants (70.6%), sufficient knowledge are 2 participants (11.8%) and good knowledge are 3 participants (17.6%). Students' knowledge increased after being given education to sufficient knowledge: 5 participants (29.4%), good knowledge:10 participants (58.8%) and lack of knowledge: 2 participants (11.8%). It can be concluded that there is an increase in the knowledge of elementary school pupils after being given education on the correct cough etiquette.